BRICS and the New American Imperialism : Global rivalry and resistance - Satgar, Vishwas (Book collections on Project MUSE., 2020)
Contemporary thinking on imperialism and anti-imperialism in relation to the BRICS countries, drawing on the work of Rosa Luxemburg considers the prospects of a new horizontal political vessel to build global convergence.